2010
DOI: 10.1103/physrevb.82.155302
|View full text |Cite
|
Sign up to set email alerts
|

Four-wave-mixing imaging and carrier dynamics of PbS colloidal quantum dots

Abstract: We demonstrate coherent multiphoton imaging of PbS colloidal quantum dots based on the detection of their transient resonant four-wave-mixing ͑FWM͒ emission under 150 fs pulsed laser excitation. Background-free imaging of PbS quantum dots in resonance with their ground-state excitonic absorption at 1.2 m wavelength is shown, with intrinsic optical sectioning and a spatial resolution better than the one-photon diffraction limit, promising for deep tissue microscopy. The four-wave-mixing efficiency is found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…Measurements are taken for τ 23 = 2 ps to avoid nonresonant nonlinear effects at time overlap and in the HHVV polarization configuration of P 1 , P 2 , P 3 , and reference to suppress background from detector nonlinearities. 10 A change in τ 23 only changes the total FWM amplitude due to the decay of the density grating but does not modify the dynamics versus τ 12 (see dotted line in Fig. 2 for τ 23 = 100 ps).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Measurements are taken for τ 23 = 2 ps to avoid nonresonant nonlinear effects at time overlap and in the HHVV polarization configuration of P 1 , P 2 , P 3 , and reference to suppress background from detector nonlinearities. 10 A change in τ 23 only changes the total FWM amplitude due to the decay of the density grating but does not modify the dynamics versus τ 12 (see dotted line in Fig. 2 for τ 23 = 100 ps).…”
mentioning
confidence: 92%
“…10 Furthermore, multicarrier effects, such as charged excitons or multiexcitons, give rise to a population decay on the 10-100-ps timescale due to Auger recombination, 14 which is not observed in the density dynamics. We found that such processes are important for time-averaged excitation intensities >1 KW/cm 2 A possible mechanism responsible for a fast dephasing of the ZPL in PbS CQDs is the phonon-assisted thermalization between the different fine-structure states of the excitonic ground state, which are split by intervalley scattering and exchange interaction and have different angular momentum projections.…”
mentioning
confidence: 99%
“…[1][2][3][4] While most studies have focused on colloidal nanoparticles of lead sulfide, 5 work on isolated (gas phase) clusters of lead sulfide, (PbS) n , has been relatively scarce. Recently, in a combined experimental and theoretical study 6 we explored the geometric structures and electron affinities of gas-phase lead sulfide clusters, (PbS) n , ranging in size from n = 1-15.…”
Section: Introductionmentioning
confidence: 99%
“…For these conditions, relaxation times in the QD GS as short as 2 ps have been reported. 19,47 With our quasi-resonant excitation with very little excess energy, the process dominating the carrier dynamics is an energetic rearrangement with the GS exciton manifold of the QDs.…”
Section: -mentioning
confidence: 99%